Investigating the Effect of Using English Islamic Pop Songs on Students’ Vocabulary Size - Nurdin, Mardiana; Asmawati, Andi; Najamuddin, Muh. (Institut Agama Islam Negeri Palopo, 2023)
English is a foreign language in Indonesia. Students need to know more about its vocabulary to use English to communicate. One of the strategies to improve students’ vocabulary size is through English Pop songs. This study investigated the effect of English Islamic Pop songs on students’ vocabulary size. The method employed was experimental research with a Pre-Experimental design. The population was the first-year students of an Islamic senior high school, and the samples selected were 20 students using a simple random technique. This study used two vocabulary tests to collect data: pre and post-test and Vocabulary Level Test (VLT). Data gained were analyzed using data analysis techniques through SPSS Statistical V22.0. The result indicated that using English Islamic Pop songs improved students’ vocabulary size; however, this was not followed by the level improvement. Students’ vocabulary size level remained at 2000 words. Various songs by different singers will be needed for further research. Therefore, using Islamic Pop songs in teaching vocabulary is suggested to introduce Islamic English words and phrases to students.